The unintended consequences of policy making : The UK's prevent strategy - Gürbüz, Ayşegül (My University, 2020)
Bu tez İngiltere’de Prevent Stratejisinin neden gençlik radikalleşmesini engellemediğini sormaktadır. Bunu yapmak üzere Barry Buzan, Ole Wæver ve Jaap De Wilde’ın ‘Security – A New Framework for Analysis’ kitabında sunduğu güvenlikleştirme teorisi kullanılmaktadır. İngiltere’nin Prevent Stratejisinin bir ilişkiyi güvenlikleştirmek için gerekli olan şartları nasıl yerine getirdiğini gösterdikten sonra, tez Prevent’ın radikalleşme sürecine nasıl katkıda bulunduğunu göstermektedir. Bu politika ile otomatik şüpheli haline gelen Müslüman halkı, ilgisizlik ve sosyal marjinalleşme düzeylerini artıran devlete olan güvenini yitirdiler. Prevent Stratejisinin radikalleşmeye katkıda bulunan bir faktör haline gelmesi bu politikanın istenmeyen bir sonucudur. Bu durum ise söz konusu politikanın tam olarak gözden geçirilmesini gerektiren bir sonuçtur.

This thesis answers the question ‘Why the Prevent Strategy in the UK does not prevent youth radicalisation.’ In so doing, the thesis adopts a theory of securitisation proposed by Barry Buzan, Ole Wæver and Jaap De Wilde in ‘Security – A New Framework for Analysis.’ By illustrating how the United Kingdom’s Prevent Strategy fulfils the three requirements – securitising actors, referent objects and functional actors - to securitise a relationship, the thesis demonstrates how Prevent has contributed to the process of radicalisation. By becoming automatic suspects of radicalisation and extremism, British Muslims have lost their trust in the state, which has increased levels of apathy and social marginalisation. The fact that the Prevent Strategy has become a contributing factor of radicalisation is an unintended consequence of policy making. Hence, this thesis shows the need for a full revision of the policy.
Keywords: British Muslims; Counter-terrorism; International relations; İngiltere; Political science; Prevent Stratejisi Prevent Strategy; Radicalisation; radikalleşme; Siyasal bilim; Terrörle mücadele politikası; UK; Uluslararası ilişkiler